2020
DOI: 10.36037/ijrei.2020.4302
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of research on amazon AWS cloud computing seller data security

Abstract: US financial media CNBC reported that Amazon sent users an email on Wednesday saying that due to technical problems, some users' names and email addresses were leaked, but the problem has been resolved. An Amazon spokesperson said in a statement: "We have addressed this issue and notified potentially affected users. "Amazon not only declined to disclose how many users are currently affected or how long user information has been exposed, nor did it say where the data was leaked, so the outside world can't estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…e pixels are 200 × 400, and the number of mesh points for texture rendering is set to 1080 and 2000, respectively. 100 surface points are collected for sparse texture reconstruction of art representation, and the color of art is extracted according to the above simulation environment and parameter settings [21][22][23]. e category and attribute prediction benchmark is used as the dataset in this experiment to test the impact of the strategy provided in this study.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 99%
“…e pixels are 200 × 400, and the number of mesh points for texture rendering is set to 1080 and 2000, respectively. 100 surface points are collected for sparse texture reconstruction of art representation, and the color of art is extracted according to the above simulation environment and parameter settings [21][22][23]. e category and attribute prediction benchmark is used as the dataset in this experiment to test the impact of the strategy provided in this study.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 99%
“…The graphical method is primarily used to find the correlation between variables by drawing a scatter diagram, while the calculating correlation coefficient method is used to provide specific quantitative data to judge the degree of correlation between variables based on the scatter diagram. This paper primarily uses the graphical method to analyze the relationship between variables, to determine whether there is a linear relationship between a dependent variable and an independent variable [ 23 ]. To support the regression analysis, this paper does correlation analysis on the current situation of the teaching power of college teachers and its influencing factors; to highlight the value of the main factor, this paper uses the maximum variance method to do a rotation on the data and get the rotated factor loading matrix; according to the rotated factor loading matrix graph, we can know the relative importance of each variable on the common factor and analyze where the significance of each factor lies.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…This study concluded that a comprehensive assessment of the patient is needed before performing ERCP to determine whether there is stenosis in the common bile duct, to determine the location, number, and size of stones, and to remove stones electively after placing drainage if intraoperative fear of difficulty in stone extraction cannot be hard to prevent complications caused by appropriate operation. At the beginning of the clinical application of laparoscopy, patients with a history of biliary surgery had been considered a relative contraindication to LCBDE treatment, and currently, due to the continuous maturation of laparoscopic technology, this contraindication has been eliminated and many successful surgical reports have emerged [ 19 ]. For some patients who are too old, obese, unable to tolerate open surgery, or have large stone size, LCBDE treatment can be performed after all preoperative preparatory activities are done [ 20 ].…”
Section: Discussionmentioning
confidence: 99%